Spatial patterns of congruence or mismatch between taxonomic, functional, and phylogenetic diversity and endemism of perennial flora along the aridity gradient of Chile - Poch, Paola; Poulin, Elie; Pérez, María Fernanda; Peralta, Gioconda; Hinojosa, Luis Felipe (Frontiers in Plant Science, 2024)
Understanding the relationships between taxonomic, functional, and phylogenetic diversity and endemism across environmental gradients is essential for elucidating the eco-evolutionary mechanisms that shape local plant communities. A database was compiled from field surveys, national herbarium records, and virtual records of perennial plant specimens collected in the aridity gradient of northern Chile, between 18 and 32°S. A large-scale dated phylogeny of available perennial plants was used, and 11 functional traits were selected to construct a dendrogram using the UPGMA (Unweighted Pair-Group Method with Arithmetic Mean) method for the species present in our database. We calculated spatial patterns of α-diversity, including taxonomic (TD), functional (FD), and phylogenetic (PD) diversity, as well as weighted (WE), functional (FE), and phylogenetic (PE) endemism. We used multiscale geographically weighted regression (MGWR) to identify spatial congruencies and discrepancies among these dimensions and to test different eco-evolutionary processes.The diversity indices TD, FD and PD showed similar geographic patterns (R 2 > 0.93), with lower diversity observed in absolute desert regions. The pattern of weighted endemism (WE) showed a weak association with functional endemism (FE) and phylogenetic endemism (PE) (local R 2 < 0.48). The regions with lower FD or PD than expected given the TD (i.e. FDWE and PE>WE), they are found in arid, high Andean and transitional zones, at different altitudes, which would indicate a greater presence of phylogenetic lineages and species with morpho-functional traits related to extreme environmental conditions and transitional biomes (arid-semiarid). These spatial discrepancies suggest different eco-evolutionary drivers between the diversity and endemism dimensions. Areas of high diversity and high endemism do not necessarily coincide, and both should be addressed by conservation efforts.